Analysis of The Effect of Load Changes on The Performance of Synchronous Generator Unit 2 at PT. PLN Nusa Daya Unit PLTU Malinau - Ismit Mado, Ismit; Andri; Arif, Muhammad; K. Maring, Ferry (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
Changes in generator power losses are adjusted to the load needs in the field, which is constantly changing and can affect the value of the per- phase current and generator field current, causing power losses. The resulting power losses affect the efficiency of the PLTU generator. To determine the generator’s efficiency due to load changes, this study was carried out using manual calculation method by collecting data on specifications, resistance, and dialy log sheets of the 2x3 MW Malinau PLTU generator unit 2 conducted at PT. Nusa Daya Unit PLTU Malinau. Based on the callculation data on May 17, the highest efficiency was 79,69% at a load 2,372 MW, while the lowest efficiency was 78,03% at a load of 2,137 MW. For the callculation results of May 18, the highets efficiency was 79,51% at a load 2,342 MW, while the lowest efficiency was 76,37% at a load of 1,941 MW. The greater the power generated by generator, the higher the efficiency of the generator and the better the generator performance. Keywords: PLTU, generator, load changes, power losses, efficiency